2011
DOI: 10.1097/md.0b013e3182380a76
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus (HBV) Reactivation in Patients Receiving Tumor Necrosis Factor (TNF)-Targeted Therapy

Abstract: The emergence of tumor necrosis factor-α (TNF-α)-targeted therapies as a key therapeutic option for patients with rheumatic, digestive, and dermatologic autoimmune diseases has been associated with increasing reports of liver damage in patients with hepatitis B virus (HBV) infection. We studied the current evidence on the use of anti-TNF agents in patients with HBV through a systematic analysis of cases reported in the MEDLINE and EMBASE databases using the MeSH term "hepatitis B virus" combined with the terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
199
3
16

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(220 citation statements)
references
References 60 publications
2
199
3
16
Order By: Relevance
“…21,[38][39][40] Several studies reported that elevated HBV viral load subsequently leads to active hepatitis. 24,25 A recent study analyzing patients with inflammatory arthritis also revealed an increased risk of HBV reactivation associated with anti-TNF therapy in patients with chronic HBV infection. 41 However, due to limited wellcontrolled studies, the association between TNF-a blockage and HBV reactivation remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,[38][39][40] Several studies reported that elevated HBV viral load subsequently leads to active hepatitis. 24,25 A recent study analyzing patients with inflammatory arthritis also revealed an increased risk of HBV reactivation associated with anti-TNF therapy in patients with chronic HBV infection. 41 However, due to limited wellcontrolled studies, the association between TNF-a blockage and HBV reactivation remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] However, there are limited reports on its effect on HBV persistence and reactivation in chronic HBV infection during anti-TNF therapy. 24,25 The role of anti-TNF therapy in chronic HBV infection is still not clear, and detailed analysis of HBV infection under TNF-a blockage therapy is essential for the prophylaxis and therapy for HBV reactivation and recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent meta-analysis (5) and a case series (6), HBV reactivation rate ranges from 15% to 39% in HBsAg-positive RA patients receiving tumor necrosis factor (TNF) inhibitors, and 3% to 5% in HBsAg-negative patients receiving this class of medication. Reactivation also occurs in those receiving nonbiologic DMARDs (7-9) and a non-TNF biologic agent, abatacept (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of reported cases found that reactivation occurred in 39% (35 of 89) of HBsAg-positive individuals including four fatal cases of acute liver failure and reactivation occurred in 5% (9 of 168) of those who were HBsAg-negative, anti-HBc-positive before starting anti-TNF therapy, including 1 fatal case. 15 Most studies have found the risk to be highest in patients receiving infliximab compared with etanercept or adalimumab. 15,16 Reactivation has also been reported with azathioprine, 6-mercaptopurine, and methotrexate used in nononcologic settings.…”
Section: Hbv Reactivation In Nononcologic Settingsmentioning
confidence: 99%
“…15 Most studies have found the risk to be highest in patients receiving infliximab compared with etanercept or adalimumab. 15,16 Reactivation has also been reported with azathioprine, 6-mercaptopurine, and methotrexate used in nononcologic settings. 17 There have been individual case reports with targeted kinase inhibitors 18 but no published reports of HBV reactivation with inhibitors of vascular growth endothelial factor.…”
Section: Hbv Reactivation In Nononcologic Settingsmentioning
confidence: 99%